Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №123

Представьте в виде дроби:
а)
$\frac{a^2 - 1}{a - b} * \frac{7a - 7b}{a^2 + a}$
;
б)
$\frac{b^2 + 2bc}{b + 3} * \frac{5b + 15}{b^2 - 4c^2}$
;
в)
$\frac{(x + 3)^2}{2x - 4} * \frac{x^2 - 4}{3x + 9}$
;
г)
$\frac{(5 - y)^2}{2y + 12} * \frac{y^2 - 36}{2y - 10}$
.

Решение а

$\frac{a^2 - 1}{a - b} * \frac{7a - 7b}{a^2 + a} = \frac{(a - 1)(a + 1)}{a - b} * \frac{7(a - b)}{a(a + 1)} = \frac{a - 1}{1} * \frac{7}{a} = \frac{7(a - 1)}{a}$

Решение б

$\frac{b^2 + 2bc}{b + 3} * \frac{5b + 15}{b^2 - 4c^2} = \frac{b(b + 2c)}{b + 3} * \frac{5(b + 3)}{(b - 2c)(b + 2c)} = \frac{b}{1} * \frac{5}{b - 2c} = \frac{5b}{b - 2c}$

Решение в

$\frac{(x + 3)^2}{2x - 4} * \frac{x^2 - 4}{3x + 9} = \frac{(x + 3)^2}{2(x - 2)} * \frac{(x - 2)(x + 2)}{3(x + 3)} = \frac{x + 3}{2} * \frac{x + 2}{3} = \frac{(x + 3)(x + 2)}{6}$

Решение г

$\frac{(5 - y)^2}{2y + 12} * \frac{y^2 - 36}{2y - 10} = \frac{(5 - y)^2}{2(y + 6)} * \frac{(y - 6)(y + 6)}{2(y - 5)} = \frac{y - 5}{2} * \frac{y - 6}{2} = \frac{(y - 5)(y - 6)}{4}$